The work design profiles of employees in the Australian Not-For-Profit sector: A person-centered perspective - Knight, Caroline; Parker, sharon; McLarnon, Matt; Wenzel, Ramon (2019)
Purpose: Work design is the content, responsibilities and relationships involved in work. Research suggests work characteristics co-occur, with important effects on work outcomes. We investigate the structure and function of different work design profiles of Australian Not-For-Profit (NFP) employees and identify predictors and outcomes to inform theory and future interventions.